Detection and localization of small nuclear ribonucleoproteins (snRNPs) in trypanosomatids using anti-m3G antibodies - Bosetto, Maira Cegatti [UNESP]; Mortara, Renato Arruda; Ambrósio, Daniela Luz [UNESP]; Passerini, Gabriela Duó [UNESP]; da Silva, Marco Túlio Alves [UNESP]; Okuda, Erica Sayuri [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (My University, 2008)
This work reports for the first time the identification and immunolocalization, by confocal and conventional indirect immunofluorescence, of m3G epitopes present in ribonucleoproteins of the following trypanosomatids: Trypanosoma cruzi epimastigotes of three different strains, Blastocrithidia ssp., and Leishmania major promastigotes. The identity of these epitopes and hence the spe~cificity of the anti-m3G monoclonal antibody were ascertained through competition reaction with 7-methylguanosine that blocks the Ig binding sites, abolishing the fluorescence in all the parasites tested and showing a specific perinuclear localization of the snRNPs, which suggests their nuclear reimport in the parasites. Using an immunoprecipitation technique, it was also possible. to confirm the presence of the trimethylguanosine epitopes in trypanosomatids.